2006
DOI: 10.1375/twin.9.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Symptoms of Depression in Unrelated Individuals and Opposite-Sex Twin and Sibling Pairs

Abstract: Diagnosis of a major depressive episode by the Diagnostic and Statistical Manual of Mental Disorders of the American Psychiatric Association requires 5 out of 9 symptoms to be present. Therefore, individuals may differ in the specific symptoms they experience and reach a diagnosis of depression via different pathways. It has been suggested that depressed women more often report symptoms of sleep disturbance, appetite or weight disturbance, fatigue, feelings of guilt/worthlessness and psychomotor retardation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Future studies should therefore be conducted with sample sizes sufficiently large to detect small sex differences in the data. Results from earlier investigations on both qualitative and quantitative sex differences in major depression are mixed (Kendler et al, 2006; Middeldorp et al, 2006). Regarding anxiety disorders, substantial sex differences in symptoms reported and prevalence rates have been found across the life span (MacKinaw-Koons & Vasey, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Future studies should therefore be conducted with sample sizes sufficiently large to detect small sex differences in the data. Results from earlier investigations on both qualitative and quantitative sex differences in major depression are mixed (Kendler et al, 2006; Middeldorp et al, 2006). Regarding anxiety disorders, substantial sex differences in symptoms reported and prevalence rates have been found across the life span (MacKinaw-Koons & Vasey, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…24,25 Countering these concerns, the episodes of depression we found 15 consisted of a similar pattern of particular symptoms, total number of symptoms and sociodemographic correlates as has been found in other countries using full DSM-IV diagnostic criteria. 26,27 This suggests that the same underlying phenotype has been tapped into, rather than a subtype of depression that is substantially qualitatively different from that seen in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between assessment by CIDI and by LIDAS was substantial. Cases in NTR and NESDA were assessed about 9 years before LIDAS (Middeldorp et al, 2006;Sullivan et al, 2009), thus recall bias may explain a change in status. Controls in NESDA were identified as scoring with no depression on all CIDI assessments, including the most recent one a few months before completing LIDAS.…”
Section: Heritability and Prs Analysesmentioning
confidence: 99%
“…Some studies reported no or little difference between sexes (Kendler & Prescott, 1999;Nivard et al, 2015), whereas some reported a higher heritability of lifetime MDD in women, than in men (Kendler, Gardner, Neale, & Prescott, 2001;Kendler, Gatz, Gardner, & Pedersen, 2006). However, there is no evidence for qualitative sex differences in the genetic architecture of depression with the empirical data indicating that the same genes are expressed in men and women (Eaves et al, 1997;Middeldorp, Wray, Andrews, Martin, & Boomsma, 2006;Vink et al, 2012).…”
Section: Introductionmentioning
confidence: 99%